Hubungan Peran Suami dan Sikap Ibu Terhadap Pemakaian Kontrasepsi Implant Pada Akseptor KB Di Rumah Sakit Bhayangkara Makassar Tahun 2015 - Utama, Risma Putri (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2019)
Background: the use of a cotraception tool is a shared responsibility between husband and wife. The results of the study showed that 65% of women wanted the role of a larger husband in the selection of contraceptive devices. An implant contraceptive is one of the contraceptives in the form of implants made of a kind of silatic rubber which contains hormones attached to the upper arm. Support and attitude of a person regarding implants will cause action on the use of implants. Objective: To determine the relationship of the role of the husband and the attitude of the mother to the use of implant contraception in family planning acceptors at Bhayangkara Makassar Hospital in 2015. Methods: The type of research was descriptive analytic. The population in this study were all mothers who used implant contraception in the family planning room of Bhayangkara Hospital in Makassar as many as 184 people. Sampling with accidental sampling technique amounted to 65 samples. Data were analyzed using Chi-Square Statistical Test with p-Value 0.05). Results: There is a relationship between the role of husband and implant contraceptive use (P-Value = 0.036 0.05), there is a relationship between maternal attitudes and implant contraceptive use (P-Value = 0.002 0.05). Conclusion: the role of the husband and the mother's attitude are related to the use of implant contraception.Keywords: husband's role, mother's attitude, implant contraception